Tetrahedral framework nucleic acids promote diabetic wound healing via the Wnt signalling pathway. Issue 11 (22nd July 2022) - Wang, Zejing; Lu, Hao; Tang, Tao; Liu, Lei; Pan, Bohan; Chen, Jiqiu; Cheng, Dasheng; Cai, Xiaoxiao; Sun, Yu; Zhu, Feng; Zhu, Shihui
Abstract: Objectives: To determine the therapeutic effect of tetrahedral framework nucleic acids (tFNAs) on diabetic wound healing and the underlying mechanism. Materials and Methods: The tFNAs were characterized by polyacrylamide gel electrophoresis (PAGE), atomic force microscopy (AFM), transmission electron microscopy (TEM), dynamic light scattering (DLS) and zeta potential assays. Cell Counting Kit‐8 (CCK‐8) and migration assays were performed to evaluate the effects of tFNAs on cellular proliferation and migration. Quantitative polymerase chain reaction (Q‐PCR) and enzyme‐linked immunosorbent assay (ELISA) were used to detect the effect of tFNAs on growth factors. The function and role of tFNAs in diabetic wound healing were investigated using diabetic wound models, histological analyses and western blotting. Results: Cellular proliferation and migration were enhanced after treatment with tFNAs in a high‐glucose environment. The expression of growth factors was also facilitated by tFNAs in vitro. During in vivo experiments, tFNAs accelerated the healing process in diabetic wounds and promoted the regeneration of the epidermis, capillaries and collagen. Moreover, tFNAs increased the secretion of growth factors and activated the Wnt pathway in diabetic wounds. Conclusions: This study indicates that tFNAs can accelerate diabetic wound healing and have potential for the treatment of diabetic wounds. Abstract : Tetrahedral framework nucleic acids (tFNAs) can facilitate the proliferation and migration of HaCaTs, HDFs and HUVECs in a high‐glucose environment. tFNAs can accelerate diabetic wound healing by promoting epithelialization, vascularization, collagen synthesis and the secretion of growth factors via the Wnt pathway.